Use of mathematical literature - Dorling, Alison Rosemary (Information sources for research and development., 1977)
Use of Mathematical Literature discusses the bibliographic concerns of mathematical literature. The book is comprised of 14 chapters that cover characteristics of mathematical literature and provide reviews of some of the major literature in various mathematical fields.